Attachment Style Moderates the Effects of Oxytocin on Social Behaviors and Cognitions During Social Rejection: Applying a Research Domain Criteria Framework to Social Anxiety. (November 2014) - Fang, Angela; Hoge, Elizabeth A.; Heinrichs, Markus; Hofmann, Stefan G.
Whereas the Diagnostic and Statistical Manual of Mental Disorders ( DSM ) categorizes individuals with similar self-reported symptoms, the research domain criteria offers a new approach for classifying mental disorders on the basis of dimensions of observable behaviors and neurobiological measures. The objective of this proof-of-concept study was to adopt this approach by distinguishing individuals on the basis of disorder-related personality traits during an experimental manipulation that targeted a disorder-related biological mechanism. In a double-blind, placebo-controlled study design, we examined whether attachment style moderated the effect of oxytocin administration on social behaviors and cognitions during a social-exclusion test in individuals with social anxiety disorder. Among participants who received oxytocin, as opposed to a placebo, only individuals with low attachment avoidance displayed more social affiliation and cooperation, and only those with high attachment avoidance showed faster detection of disgust and neutral faces. Thus, attachment style moderated oxytocin's effects among individuals who shared the same DSM diagnosis. We conclude that neurobiological tests can inform new classification strategies by adopting a research domain criteria framework.